2020
DOI: 10.1111/papr.12864
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Music Therapy on Pain After Orthopedic Surgery—A Systematic Review and Meta‐Analysis

Abstract: Background Although music interventions on postoperative pain (POP) have positive effects, limited research has focused on systematic reviews and meta‐analyses of its efficacy for orthopedic patients. This systematic review aimed to examine the effects of music therapy on pain after orthopedic surgery. Method The Cochrane Library, PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Nursing Reference Center (NRC), Airiti Library, and National Digital Library of Theses and Dissertations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 50 publications
(160 reference statements)
5
44
0
4
Order By: Relevance
“…Therefore, we assume whether increasing the frequency of music may be associated with a positive efficiency. A similar assumption was supported in a previous systematic review [34], but varying surgical procedures may result in unreliable evidence. As correlation studies are limited in TKR surgery, this study failed to obtain an accurate answer.…”
Section: Anxiety Degreesupporting
confidence: 74%
See 1 more Smart Citation
“…Therefore, we assume whether increasing the frequency of music may be associated with a positive efficiency. A similar assumption was supported in a previous systematic review [34], but varying surgical procedures may result in unreliable evidence. As correlation studies are limited in TKR surgery, this study failed to obtain an accurate answer.…”
Section: Anxiety Degreesupporting
confidence: 74%
“…Due to its high heterogeneity, attaining a firm conclusion about the effectiveness of musical interventions in those treated with TKR is difficult. Furthermore, another meta-analysis and systematic review reported the effect of musical therapy on pain following orthopedic surgery, where musical interventions were found to relieve pain [34]. The study included a series of surgical operations when assessing the utility of listening to music after TKR, including the position of the knee, hip, shoulder, spine, and others.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have evaluated the analgesic effect of music in other surgical procedures (knee, hip, and spine) (Lin et al., 2019), and others demonstrated benefits of using music in burn dressing changes (Hsu et al., 2016; Rohilla et al., 2018). However, to the best of our knowledge, this is the first blinded, randomized controlled trial that demonstrates the analgesic efficacy of music during the dressing change of surgical tibial fracture, rather than isolated use in standard pharmacological analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Among these resources, music has been increasingly studied and developed as a viable complementary therapy in the management of pain in several healthcare settings. Studies point to a statistically significant reduction in pain scores in adult patients undergoing orthopedic surgeries, after listening to music (Lin et al., 2019; Schneider, 2018). This is a low‐cost tool that can be used by the nursing team, for pain and anxiety relief (Sharda et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the description of pain provided by the children is usually inconclusive [8]. Several non-pharmacological methods, including position adjustment, reassurance [9], and music, have been proposed to alleviate the pain [10][11][12].…”
Section: Introductionmentioning
confidence: 99%